2019
DOI: 10.1002/bmc.4676
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the pattern and kinetics of degradation of adalimumab using a stability‐indicating orthogonal testing protocol

Abstract: Forced degradation studies are crucial for the evaluation of the stability and biosimilarity. Here, adalimumab was subjected to oxidation, pH, temperature, agitation and repeated freeze-thaw in order to generate all possible degradation products. An orthogonal stability-indicating testing protocol comprising SE-HPLC, RP-HPLC, TapeStation gel electrophoresis, dynamic light scattering (DLS), and functional receptor binding assay was developed and validated. The assay protocol was used for the assessment of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The amino acid residues tryptophan, tyrosine, phenylalanine, cysteine, and peptide backbones are the most susceptible sites for photoinduced degradation (16). The obtained results show that adalimumab follows the first-order reaction kinetics as confirmed in the research conducted by Hassan and coworkers (17). It is worth highlighting that the major obtained stress products of adalimumab were low-molecular--weight fragments with different UV spectra compared to biopharmaceutic.…”
Section: Forced Degradation Studysupporting
confidence: 65%
See 1 more Smart Citation
“…The amino acid residues tryptophan, tyrosine, phenylalanine, cysteine, and peptide backbones are the most susceptible sites for photoinduced degradation (16). The obtained results show that adalimumab follows the first-order reaction kinetics as confirmed in the research conducted by Hassan and coworkers (17). It is worth highlighting that the major obtained stress products of adalimumab were low-molecular--weight fragments with different UV spectra compared to biopharmaceutic.…”
Section: Forced Degradation Studysupporting
confidence: 65%
“…The major stress products of Humira ® were low-molecular-weight fragments while high-molecular-weight aggregates were not detected. Based on the study of Hassan and coworkers (17) we consider this could be associated with the presence of polysorbate 80 in the formulation leading to a decreased risk of aggregate formation.…”
Section: Forced Degradation Studymentioning
confidence: 99%
“…Normally, “the least stable domain is involved in the aggregation process” [ 13 ], which means that for ADA it would be the C H 2 domain. In any case, it has been demonstrated that enthalpy reductions are related to losses of native antibody structure, which sometimes has been associated with aggregation events [ 21 , 22 ]. The hydrodynamic size and ζ potential of the ADA dilutions were also determined.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the small size of the thermal event in the ADA 80 thermogram [23] From these results, it is possible to conclude that temperature-stress conditions for ADA translate into an enthalpy decrease with no significant changes in transition midpoints when analyzed by nano-DSC. It has already been reported that temperature-stress conditions induce ADA aggregates of different MW and solubility [22,24]. Wu et al stated that aggregation is temperature dependent, having an Arrhenius regime for T ≥ T m1 (C H 2 transition midpoint) or a non-Arrhenius regime for T < T m1 [25].…”
Section: Preliminary Studies: Factors Influencing Nano-dsc Resultsmentioning
confidence: 99%
“…Biological products tend to be less stable than small molecules and, importantly, subtle changes induced by environmental stress can significantly affect their therapeutic properties [25]. In addition, monoclonal antibodies are frequently formulated at high concentration levels, potentially leading to aggregate formation and resultant impurities [27]. Further, stability testing also allows recommended storage conditions to be established [25].…”
Section: Discussionmentioning
confidence: 99%